A tale of two approaches to heteroclinic solutions for Φ-Laplacian systems. Issue 5 (October 2020) - Ruan, Yuan L.
Abstract: In this article, the existence of heteroclinic solution of a class of generalized Hamiltonian system with potential V : R^n R having a finite or infinite number of global minima is studied. Examples include systems involving the p -Laplacian operator, the curvature operator and the relativistic operator. Generalized conservation of energy is established, which leads to the property of equipartition of energy enjoyed by heteroclinic solutions. The existence problem of heteroclinic solution is studied using both variational method and the metric method. The variational approach is classical, while the metric method represents a more geometrical point of view where the existence problem of heteroclinic solution is reduced to that of geodesic in a proper length metric space. Regularities of the heteroclinic solutions are discussed. The results here not only provide alternative solution methods for Φ-Laplacian systems, but also improve existing results for the classical Hamiltonian system. In particular, the conditions imposed upon the potential are very mild and new proof for the compactness is given. Finally in ℝ 2, heteroclinic solutions are explicitly written down in closed form by using complex function theory.